Balkan Session: Czechs Playing for the Balkans - Libánská, Alena (Lidé města, 2015)
This paper discusses Balkan music performed in the Czech Republic, especially in Prague. Balkan music is performed by musicians not enculturated in Balkan culture. Their music production can be understood as a social practice initiated by certain stereotypes, viewed as Balkanism (Todorova 2009). In doing so, they display their attitude towards their Slavic neighbors. Using an ethnographic snapshot of a festival evening called Balkan Session, the main objective of this paper is to show the interaction between Balkan music as performed in Prague and the Balkans, represented by the migrants from the Balkan Peninsula in Prague. The concepts of Balkanism (Todorova 2009), Safe Enterprise (Laušević 2007) and Intimate Distance (Bigenho 2012) are used in the interpretation.